PENGELOLAAN LAYANAN PENGEMBANGAN DIRI SISWA DI SMP NEGERI 2 TOROH KECAMATAN TOROH KABUPATEN GROBOGAN - SUNTORO , SUNTORO (2011)
Research purposes are: (1) describing self development activity planning in 2 Toroh Government Junior High School Toroh Subdistrict Grobogan District. (2) describing student self development activity execution in extracurricular in 2 Toroh Government Junior High School Toroh Subdistrict Grobogan District. (3) describing self development activity evaluation in 2 Toroh Government Junior High School Toroh Subdistrict Grobogan District. This research has done in 2 Toroh Government Junior High School Toroh Subdistrict Grobogan District, by using descriptive qualitative approach. Collecting data in this research was using active role observation, deep interview and documentation. Data analysis has done through 3 steps, are: data reduction, data presentation and conclusion/ verification. Research results are (1) self development activity program planning is in counceling service activy and extracurricular, extracurricular program planning made by extracurricular cultivator known by headmaster. Extracurricular programs develope based on student need, includes: dancing, drum band, basketball, band, paiting, volley, pingpong, conversation (English), vocal (sing), and scout. Development activity planning through extracurricular contains activity theme, semester, year, purpose, target, execution time, kind of activity and funding source. (2) Self development activity execution done in extra time (not in lesson time) and as permanent program implementation and have to be followed by students to form student character and attitute. These activities execution based on schedule, especially for extracurricular activity done in every Monday until Saturday about 15.00 up to 17.00. Extracurricular activity purposes to give student chances to improve and express themselves based on their need, talent, and inerest accoding to school condition. 3) Self development activity evaluation especially extracurricular activity done by each cultivator to know changes of student attitude, among cognivity, affective, and psychomotor aspect. Assessment is according to test and non test, final result is qualitative values in raport. Self development activity evaluation in extracurricular is evaluation purposed to know activity accuracy in student interest activity, self development activity evaluation result in extracurricular is qualitative used by headmaster as increasing or decreasing consideration of activities.